Transformaciones de la práctica odontológica en el contexto de la reforma estructural del Estado de finales del siglo XX: confluencias hacia la proletarización de la odontología en Colombia (2014)
ABSTRACT: This essay characterizes the main contemporary transformations affecting dental practice in Colombia, placing its principal tendencies in the context of the social and sanitary reforms of the country. Parting from this, we present the hypothesis of the narrowing of the field of dentistry defined by the present historical moment, that at present, constitutes a tendency towards de- professionalization, being it the product of the convergence of multiple factors that have reshaped the practice of dentistry in the context of the structural reform of the country and the open market, mainly in the educational and health aspects. We present several aspects that characterize this narrowing in the practice of our profession regarding the preparation of new professionals and the clinical practice.